2013
DOI: 10.1259/bjr.20130318
|View full text |Cite
|
Sign up to set email alerts
|

Effective dose to staff members in a positron emission tomography/CT facility using zirconium-89

Abstract: Cite this article as: Alzimami KS, Ma AK. Effective dose to staff members in a positron emission tomography/CT facility using zirconium-89. Br J Radiol 2013;86: 20130318. FULL PAPER Effective dose to staff members in a positron emission tomography/CT facility using zirconium-89 1 K S ALZIMAMI, PhD F-FDG to the staff near the patient. This interesting result raises apparently contradictory implications in the radiation protection considerations of a PET/CT facility. Advances in knowledge: To the best of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…While several isotopes of Zr including 86 Zr ( t 1/2 : 17 h, γ 100%, E γ = 241 keV), 88 Zr ( t 1/2 : 85 d, γ 100%, E γ = 390 keV), and 89 Zr ( t 1/2 : 78.4 h, β + 22.8%, E β + max = 901 keV; 901 keV, EC 77%, E γ = 909 keV) can be produced on a cyclotron [ 66 , 67 ], 89 Zr has received the most attention for radiopharmaceutical development because of its favorable nuclear decay properties that make it useful in the labeling of antibodies for immuno-PET applications ( Figure 1 ) [ 68 , 69 , 70 ]. The availability of carrier-free 89 Zr as either zirconium-89 oxalate ([ 89 Zr]Zr(ox) 2 ) or zirconium-89 chloride ([ 89 Zr]Zr Cl 4 ) is essential to the development of effective immuno-PET agents.…”
Section: Zirconium Chemistry and The Production Of Zirconium-89mentioning
confidence: 99%
“…While several isotopes of Zr including 86 Zr ( t 1/2 : 17 h, γ 100%, E γ = 241 keV), 88 Zr ( t 1/2 : 85 d, γ 100%, E γ = 390 keV), and 89 Zr ( t 1/2 : 78.4 h, β + 22.8%, E β + max = 901 keV; 901 keV, EC 77%, E γ = 909 keV) can be produced on a cyclotron [ 66 , 67 ], 89 Zr has received the most attention for radiopharmaceutical development because of its favorable nuclear decay properties that make it useful in the labeling of antibodies for immuno-PET applications ( Figure 1 ) [ 68 , 69 , 70 ]. The availability of carrier-free 89 Zr as either zirconium-89 oxalate ([ 89 Zr]Zr(ox) 2 ) or zirconium-89 chloride ([ 89 Zr]Zr Cl 4 ) is essential to the development of effective immuno-PET agents.…”
Section: Zirconium Chemistry and The Production Of Zirconium-89mentioning
confidence: 99%
“…6 In a Monte Carlo study, for radiation protection purposes, when using 89 Zr in an imaging facility that is optimized for the annihilation photons only, the results showed that the low 89 Zr injected activity (75 MBq) would deliver a lower effective dose near the patient than 18 F (500 MBq) would; however, 89 Zr would give a higher effective dose than the 18 F outside the patient room due to the greater penetration power of the prompt g-ray. 6 In PET procedures utilizing 18 F-FDG, the 511 keV annihilation radiation is the main radiation protection concern, delivering a dose to the staff of 2.7-4.0 mSv during injection and 3.5-5.0 mSv during patient set-up. 7 The dose to the general public in the waiting area is about 0.8 mSv per procedure.…”
Section: Introductionmentioning
confidence: 99%
“… 5 89 Zr decays to 89 Y through β + emission (22.7%) and electron capture (77.3%) followed by a prompt γ-ray at 909 keV (99.04%). 6 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations